Systematic Review and Meta-Analysis of Vortioxetine for the Treatment of Major Depressive Disorder in Adults - Zhang, Xinyan; Cai, Yuchun; Hu, Xiaowen; Lu, Christine Y.; Nie, Xiaoyan; Shi, Luwen (Frontiers in Psychiatry, 2022)
Objective: We aimed to compare the efficacy, acceptability, and tolerability of vortioxetine in the treatment of Major Depressive Disorder (MDD) in adults. Method: We searched PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Clinical Trials (CENTRAL), and ClinicalTrials.gov for randomized controlled trials that examined vortioxetine versus placebo or other antidepressants for the treatment of MDD from database inception to August 30, 2021, using keywords Vortioxetine, Brintellix, Trintellix, LuAA21004, major depressive disorder, mood disorder, affective disorder, and MDD. We identified 789 publications after removing duplicates. After screening, 20 eligible randomized controlled trials were identified, of which 19 were included in the final meta-analysis. We included adults (aged 18 years and older) with a primary diagnosis of MDD. Two review authors independently selected the studies and extracted data. We extracted data on study characteristics, participant characteristics, intervention details and outcome measures in terms of efficacy, acceptability, and tolerability. Analyses were performed using random-effects models, and outcomes were pooled as risk ratios (RRs) and standardized mean differences (SMDs). Results: Vortioxetine outperformed the placebo in efficacy outcomes, including response (RR 1.35, 95% CI 1.23-1.48; P <0.001), remission(RR 1.33, 95% CI 1.17 -1.52; P < 0.001), and cognitive function( SMD 0.34, 95% CI 0.16-0.52; P=0.0003). Compared with the serotonin noradrenaline reuptake inhibitors (SNRIs), vortioxetine had better tolerability(RR 0.90, 95% CI 0.86-0.94; P < 0.001) but no significant difference in response(RR 0.91, 95%CI 0.82-1.00; P=0.06) or remission(RR: 0.99, 95% CI 0.81-1.20, P= 0.88). Vortioxetine had no difference in response (RR 1.08, 95% CI 0.88-1.32; P= 0.46), remission (RR 1.00, 95%CI 0.41-2.44; P=1.00) comparing with selective serotonin reuptake inhibitors (SSRIs). Conclusions: Vortioxetine is more advantageous over placebo in treating MDD among adults, but no significant difference compared to SNRIs and SSRIs in general.